2023
DOI: 10.1037/xge0001449
|View full text |Cite
|
Sign up to set email alerts
|

Policy abstraction as a predictor of cognitive effort avoidance.

Ceyda Sayalı,
Jordan Rubin-McGregor,
David Badre

Abstract: Consistent evidence has established that people avoid cognitively effortful tasks. However, the features that make a task cognitively effortful are still not well understood. Multiple hypotheses have been proposed regarding which task demands underlie cognitive effort costs, such as time-on-task, error likelihood, and the general engagement of cognitive control. In this study, we test the novel hypothesis that tasks requiring behavior according to higher degrees of policy abstraction are experienced as more ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
(118 reference statements)
0
4
0
Order By: Relevance
“…However, we show that WM load was only minimally costly and that updating and interference had a greater influence on subjective cognitive effort. Other work has shown that WM maintenance demands minimally influence cognitive effort avoidance behavior [ 17 ] and do not evoke task performance costs [ 35 ]. Lure stimuli in WM storage demand an accurate maintenance of both stimulus identity and stimulus order.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we show that WM load was only minimally costly and that updating and interference had a greater influence on subjective cognitive effort. Other work has shown that WM maintenance demands minimally influence cognitive effort avoidance behavior [ 17 ] and do not evoke task performance costs [ 35 ]. Lure stimuli in WM storage demand an accurate maintenance of both stimulus identity and stimulus order.…”
Section: Discussionmentioning
confidence: 99%
“…Tasks which subjects demanded the most incentives to complete [ 5 7 ] or which subjects tended to avoid in favor of other tasks with equivalent rewards [ 4 , 8 , 9 ] are considered most effortful. Some costly aspects of these tasks are external, like time on task [ 10 12 ] or the complexity of the cognitive model required by the task [ 13 16 ], but other costs arise from the internal operations necessary to realize external actions, like the degree of hierarchical cognitive control required [ 17 ]. In general, cognitive resistance increases when tasks place substantial demands on working memory and cognitive control [ 5 , 18 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the Specific level, the number of simultaneously possible sequences is reduced to one. Therefore, each level represents a linear increment in abstraction policy: Sequence (first-order policy), Sub-Rule (second-order policy), Rule (third-order policy), and General (fourth-order policy; Sayalı et al. 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…Westbrook & Braver, 2015). Several versions of the DST have been used to demonstrate that people avoid a wide range of cognitive control demands, such as response conflict (Schouppe et al, 2014), task switching (Kool et al, 2010;Sayalı & Badre, 2021), working memory maintenance (Kool et al, 2010), increasingly complex task policies (Sayalı et al, 2023), and even the exertion of empathy (Cameron et al, 2019).…”
mentioning
confidence: 99%